Eden Smith and the Canadian Domestic Revival - Adams, Annmarie (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1993)
The designer of more than 2500 detached houses in late nineteenth-century and early twentieth-century Toronto, Eden Smith has been hailed as the author of a distinctly Canadian style of domestic architecture. Yet his self-promotion and the reception of his work in both the professional and popular presses of the time emphasize the Englishness of his houses. This paper considers the domestic architecture of Eden Smith as an index of attitudes held by Toronto's upper middle class toward Britain in the early twentieth century. What did the image of an "English house" represent in Edwardian Toronto? Why were these particular qualities attractive to Toronto's landed gentry?Eden Smith's architecture was both distinct and derivative. The language of the elevations was unmistakably British, while the plan of his houses was something completely new. Smith's popularity and his influence on subsequent generations of Canadian house-architects speak eloquently of the willingness of Toronto's middle class to try new things, but only clothed in the auspices of a British past.